Effect of papermaking technique parameters on air permeability and sound insulation of glass fiber felt. (8th February 2023) - Hu, Jian; Li, Xiaojun; Han, Ruonan; Xue, Jieyu; Zhang, Zhaoying; Peng, Jing; Tian, Jiayu; Yang, Yong
Glass fiber felt (GFF) as a fibrous and porous material has caught much attention because its light mass, low cost and excellent acoustic properties. In this paper, GFF was prepared via the papermaking technique to explore the correlation between glass fiber suspension characteristics and physical properties (uniformity, air permeability and sound insulation) of GFF. The consequence presented that increasing the dispersing times and speeds could decrease aspect ratio and flocculation of fibers, which was useful to improve viscosity and fiber hanging property of glass fiber suspension, and uniformity of GFF. However, there was no visible impact on the air permeability of GFF. The results also indicated that increasing the dispersing times could decrease sound transmission loss (STL), however which could be enhanced by changing the dispersing speeds. The optimal dispersing speed was 3000 r/min and STL could be reached 15.78 dB at 6300 Hz. Generally, GFF could be used as acoustic material for building and transportation.